1990
DOI: 10.1002/jbm.820240307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternative crosslinking methods on the low strain rate viscoelastic properties of bovine pericardial bioprosthetic material

Abstract: Early failures of bovine pericardial heart valves have been due to leaflet perforation/tearing and calcification. Since glutaraldehyde fixation has been shown to produce marked changes in leaflet mechanics and has been linked to the development of calcification, alternative crosslinking techniques have been suggested as means to overcome these obstacles. We have examined the low strain rate viscoelastic behavior of bovine pericardium: (1) fresh; (2) chemically treated with glutaraldehyde, cyanimide, or polygly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Similar results have been reported for GA crosslinking of kangaroo tail tendon [27], lyophilized dermal sheep collagen [28] and pericardial tissue [29].…”
supporting
confidence: 76%
“…Similar results have been reported for GA crosslinking of kangaroo tail tendon [27], lyophilized dermal sheep collagen [28] and pericardial tissue [29].…”
supporting
confidence: 76%
“…19 The technique has proved valuable in assessing the efficiency and density of artificially induced intermolecular crosslinks, produced by various chemical tanning agents, on a number of tissues. [20][21][22][23] The shrinkage temperature of cortical bone collagen has been shown to decline with age in rats 11 and in humans, healthy or otherwise. 4 A concomitant decrease in the biochemical stability of a tissue 4 implies that bone collagen becomes less stable with age.…”
Section: Collagen's Thermal Stabilitymentioning
confidence: 99%
“…These alternative methods are used to bridge hydroxylysine residues of different polypeptide chains or amino groups of lysine by oligomeric or monomeric crosslinks (Sung et al, 2003). Because of the adverse effects of cross-linking with glutaraldehyde or other aldehyde treatments such as formaldehyde (Nimni et al, 1988) or dialdehyde starch (Rosenberg, 1978), numerous non-aldehyde treatments have been proposed, such as carbodiimides (Sung et al, 2003), glycerol (Ferrans et al, 1991), glycidal ethers (Thyagarajanet al, 1992) including poly(glycidylether) (Noishiki et al, 1986), acyl azide (Petite et al, 1990), cyanimide (Pereira et al, 1990), genipin (Wei et al, 2005), or dye-mediated photo-oxidation, phytate (Grases et al, 2008). Genipin, obtained from the fruits of Gardenia jasminoides ELLIS (Fujikawa et al, 1987;Tsai et al, 1994), exhibited better results than glutaraldehyde regarding its cytotoxicity (Sung et al, 1999), inflammatory response, ability to prevent calcification and tissue-induced mechanical properties (Wei et al, 2005 , 1989), was shown to be less cytotoxic, superior in pliability and to better inhibit calcification than glutaraldehyde (Sung et al, 1997).…”
Section: Cross-linking Treatment Of Pericardial Tissuementioning
confidence: 99%